The Positive Impact on the Labor Market from Alternatively Organized - Parsons, Richard (Journal of Organizational Psychology, 2017)
This paper studies firms with nonprofit objectives from a theoretical prospective to determine their impact on the labor market. The perspectives of profit maximization versus social responsibility yield differing goals and divergent models. Alternative firms are shown to have equal or superior employment prospects. If these alternative firms have some pricing power due to advertising or branding, then the potential impact on employment can be significant. Currently alternatively organized firms are a very small part of our economic landscape, but since these firms can support increased employment public policy options should be considered to support the growth of alternative firms.